The Contribution of Frontline and Middle Management (FMM) in Shaping Employees’ Experience within the Organizational Communication System (OCS): An Exploratory Investigation - Mohiya, Mohamed (Journal of Posthumanism, 2025)
Organizational Communication System (OCS) represents a prevalent form of technologically enabled social networking platforms utilized within organizational contexts to facilitate employee interaction and engagement. Despite its growing implementation, empirical studies examining the function and influence of Frontline and Middle Management (FMM) on employees within the context of Organizational Communication System (OCS) remain scarce, and the discourse continues to lack a robust theoretical underpinning. Grounded in the framework of Social Exchange Theory (SET), this study seeks to critically examine and elucidate the role of Frontline and Middle Management (FMM) within the Organizational Communication System (OCS), specifically focusing on its implications for employee engagement and usage patterns. The study employed a mixed-methods approach, comprising 27 semi-structured interviews and an analysis of 178 firsthand, typewritten computerized comments as part of a content analysis. The findings indicate that the involvement of leadership within the Organizational Communication System (OCS) plays a pivotal role in shaping employees’ interactions with and utilization of the platform. This research contributes to the literature through theoretical advancements, the application of a dual-method qualitative design, empirical insights, and practical implications for organizational communication and leadership practice.